0217 The NIEHS GuLF STUDY: Mental Health Symptoms Among Participants Involved in the Deepwater Horizon Oil Spill Clean-up. (23rd June 2014) - Kwok, Richard; Engel, Lawrence; Ekenga, Christine; Miller, Aubrey; Blair, Aaron; Sandler, Dale
Abstract : Objectives: Workers and communities impacted by previous oil spills have shown increases in adverse mental health outcomes. The GuLF STUDY is investigating potential health effects among workers involved in the Deepwater Horizon oil spill clean-up response. Participants confronted physical and psychosocial stressors including exposures to oil and dispersants, income uncertainties, and challenges of family and community disruption. Method: Information on demographics, health, and clean-up experience was collected by telephone. Standardised surveys administered to 11 210 participants during home visits captured mental health outcomes including depression, anxiety, PTSD, resiliency, and perceived stress. A summary measure of adverse mental health was defined as having a poor outcome on at least one of the five standardised scales. Mental health outcomes were evaluated in relation to clean-up jobs in models that excluded individuals with pre-existing doctor-diagnosed mental health conditions and controlled for socioeconomic and other factors that contribute to mental well-being. Results: Preliminary analysis using the summary mental health measure indicate that persons who worked on oil-spill cleanup were more likely to report adverse mental health outcomes than those who did not, with ORs of 1.4 (95% CI: 1.1–1.9) for rig and barge workers who worked closer to the source of the oil spill and 1.3 (95% CI: 1.1–1.5) for those with land-based clean-up jobs compared to those who did not actively work on the clean-up effort. Conclusions: Adverse mental health outcomes were found among individuals in the GuLF STUDY population but further work is necessary to clarify the factors leading to these outcomes.